Touch the future : a manifesto in essays - Clark, John Lee, 1978- (W.W. Norton and Company, 2023)
In a series of paradigm-shifting essays, Clark reports on seismic developments within the DeafBlind community and challenges the limitations of sighted and hearing norms. In "Against Access," he interrogates the prevailing advocacy for "accessibility" that re-creates a shadow of a hearing-sighted experience, and in "Tactile Art," he describes his relationship to visual art and breathtaking encounters with tactile sculpture. He offers a brief history of the term "DeafBlind," distills societal discrimination against DeafBlind people into "Distantism," sheds light on the riches of online community, and advocates for "Co-Navigation," a new way of exploring the world together without a traditional guide.--